Behavioral Biases as An Effective Factor for the Firm Financial Decision-Making: A Literature Review (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Decision-making process is a multi-faceted and complex process. Decision making can be defined like a process of choosing from among a number of alternatives. It will not contribute enough to be fully understood and to effective decision making to be addressed only from the rational point of view. Behavioral finance is an integral part of the decision-making process. Individuals can improve their performance by recognizing the biases which discussed in the framework of behavioral finance. Understanding the possible negative effects of biases allows to the individuals to make better choices and they can avoid repeating the expensive errors in future. Result of investigations of behavioral biases on decision-makers in the firms, managerial bias issue has been raised. The studies show the effect of managerial biases on many financial decisions in firms. This paper investigated the role of biases such as overconfidence, loss aversion, optimism, anchoring, narrow framing, self-serving attribution, disposition effect etc. on financial decisions such as investing, financing, equity market, capital structure etc. This study review of 30 international studies related with behavioral corporate finance and behavioral biases that affect financial decisions in firms. The studies were gleaned from Web of Science and Google Scholar. The main contribution of this study to the literature is this study brings out the impact of behavioral biases on financial decisions in the firms by summarizing the previous studies. In this sense, this work also has an assembly quality. Therefore, this is also intended with this study that to transfer the knowledge and intellectual formation about the impact of behavioral bias on the financial decisions. In this paper, most important behavioral biases in the behavioral finance literature will be addressed.